2018
DOI: 10.1002/fsn3.811
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional content of selected species of tropical eggplant fruit (Solanum spp) diet Attenuates hepatic inflammation in high‐fat fed male Wistar rats induced with streptozotocin

Abstract: Tropical Solanum species contains a high level of phenolic acids and flavonoids, which were found to inhibit some key enzymes associated with the incidence of type 2 diabetes in in vitro and in vivo models based on earlier studies. This study was further designed to compare the nutritional properties, glycemic index, and hypolipidemic and the antioxidant effects of three species of tropical eggplant fruit (Solanum kumba, Solanum aethiopicum, and Solanum gilo) diet on streptozotocin (STZ)‐induced nephrotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The variety Tiger (23.15%) recorded the lowest grade. These results are similar to those of Nwanna et al (2019) which obtained high fiber value. The high value of fiber reported for eggplant fruit can improve its digestibility and absorption processes in large intestine, helping to stimulate peristalsis, thereby preventing constipation (Alaofe et al 2008).…”
Section: Proximate Composition Of Eggplant Varietiessupporting
confidence: 90%
“…The variety Tiger (23.15%) recorded the lowest grade. These results are similar to those of Nwanna et al (2019) which obtained high fiber value. The high value of fiber reported for eggplant fruit can improve its digestibility and absorption processes in large intestine, helping to stimulate peristalsis, thereby preventing constipation (Alaofe et al 2008).…”
Section: Proximate Composition Of Eggplant Varietiessupporting
confidence: 90%
“…According to literature sources, the total antioxidant capacity of different species can vary over a large range, in particular, methanolic extracts of various Indian spices can vary from 0.57 to 6.0 mg UAE / g DW (Deepa et al, 2013). A detailed study of the fruits of some members of the Solanaceae family showed that the antioxidant capacity was 48.8 ± 0.6 and 56.7 ± 1.4 mg AE / g of dry extract (Nwanna et al, 2013;Nwanna et al, 2019). Therefore, the antioxidant capacity of Chaenomeles fruits, determined in the range from 565.8 ± 15.7 (C. speciosa) to 1121.7 ± 27.5 (C. cathayensis) mg UAE / 100 g DW, can be considered quite high.…”
Section: Mauleimentioning
confidence: 99%
“…The methods described by Nwanna, Ibukun, et al (2016), Nwanna, Ibukun, and Oboh (2019), and Srinivasan, Viswanad, Asrat, Kaul, and Ramarao (2005) were used for the in vivo experiment. Fifty-two male Wistar rats, weighing 180-200 g, provided by the Veterinary Medicine Unit, University of Ibadan, Nigeria, were acclimatized for 2 weeks with free access to food and water.…”
Section: In Vivo Bioassaymentioning
confidence: 99%
“…The nondiabetic animal, that is the control, received 1 ml of 0.1 M citrate buffer intraperitoneally. The grouping designed were carried out as described by Nwanna, Ibukun, and Oboh (2019).…”
Section: In Vivo Bioassaymentioning
confidence: 99%
See 1 more Smart Citation